2012
DOI: 10.2174/156652312800099616
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field-Assisted Gene Delivery: Achievements and Therapeutic Potential

Abstract: The discovery in the early 2000's that magnetic nanoparticles (MNPs) complexed to nonviral or viral vectors can, in the presence of an external magnetic field, greatly enhance gene transfer into cells has raised much interest. This technique, called magnetofection, was initially developed mainly to improve gene transfer in cell cultures, a simpler and more easily controllable scenario than in vivo models. These studies provided evidence for some unique capabilities of magnetofection. Progressively, the interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 92 publications
(104 reference statements)
1
33
0
1
Order By: Relevance
“…A promising non-viral alternative for neuronal gene transfer that has emerged in recent years, involves the use of iron oxide magnetic nanoparticles (MNPs) with chemically adaptable surfaces, allowing bound genetic material to be targeted to cells by application of static or oscillating magnetic fields (Magnetofection) [6]. This approach is rapid, technically simple, safe and low cost.…”
Section: Ministry Of Higher Education and Scientific Researchmentioning
confidence: 99%
“…A promising non-viral alternative for neuronal gene transfer that has emerged in recent years, involves the use of iron oxide magnetic nanoparticles (MNPs) with chemically adaptable surfaces, allowing bound genetic material to be targeted to cells by application of static or oscillating magnetic fields (Magnetofection) [6]. This approach is rapid, technically simple, safe and low cost.…”
Section: Ministry Of Higher Education and Scientific Researchmentioning
confidence: 99%
“…Use of this method to enhance site specific drug/gene delivery have also been reported by different authors [2729]. Magnetic drug targeting (MDT) or magnetic gene targeting (MGT) combined with magnetofection has opened up the possibilities to develop methods for more efficient and less invasive drug/gene therapy strategies for major pathologies like cancer, neurodegeneration and myocardial infarction [24]. In the present study, the CPMM nanoparticles were found to be non-toxic both in vitro and in vivo systems and could be manipulated by inducing a magnetic field which offers the opportunity to develop an efficient MGT vector, in which the gene coding for a therapeutic molecule can be delivered to a therapeutic target area in the body.…”
Section: Discussionmentioning
confidence: 99%
“…In absence of a magnetic field these particles show less aggregation which prevents their accumulation in the blood vessels [10]. Since its discovery, the technique of magnetofection has been primarily used to increase the gene transfection of the in vitro cell cultures using the superparamagnetic nanoparticles [15, 24, 25]. The gradient of the magnetic field enhances the efficiency of magnetofection compared to that without magnetic field [10, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Further, multiple administrations of the same viral vector can induce the production of neutralizing Abs that significantly attenuate the therapeutic efficacy of the viral vectors. To overcome rapid dissemination to nontarget tissues and antiviral immune responses, viral vectors have been encapsulated in various polymeric matrices, such as nanoparticles, microparticles, microspheres and hydrogels (Figure 1) [91][92][93][94][95][96][97][98].…”
Section: Local Delivery Of Viral Vectors Using Nanomaterialsmentioning
confidence: 99%
“…Viral vectors encapsulated in hydrogel can be released from the gel matrix over a prolonged periods of time to induce sustained therapeutic effect in target tissue with single administration [91,92]. Magnetic nanoparticle complexed virus can efficiently be internalized into nonpermissive target tissue upon exposure to magnetic field [93,96]. Both hydrogel-and magnetic nanoparticle-mediated local delivery of viral vectors can attenuate nonspecific dissemination of viral vectors from initial injection site to nontarget tissues, resulting in superior safety profile.…”
Section: Hydrogels For Local and Sustained Delivery Of Viral Vectorsmentioning
confidence: 99%